Engaging the field through retrospective methods: a Cambodian story. Issue 5 (19th October 2016) - Young, Kevin; Okada, Chiaki
Abstract: This paper illustrates how sport may be associated with community development and peace building when marshalled by committed and influential local individuals. However, in keeping with the main theme of this special issue, the thrust of the paper is as methodological as it is substantive. Our beginning point is the argument that while innovative in many respects, the 'sport, social development and peace' (SDP) literature has been rather limited methodologically speaking. Paradoxically for a social arena that so obviously depends on the prolonged stewardship of key individuals, a life history or 'storied' approach has rarely been undertaken. In this paper, we attempt to redress this methodological imbalance by making a case for the potential usefulness of such 'recall methods' and, specifically, by both 'chronologizing' and 'narrativizing' the life of a man who has been central in promoting sport as a vehicle for community development in one of the most economically and politically challenged of all Southeast Asian countries – Cambodia. Thus, by arguing that life history approaches have the potential to make a meaningful contribution to knowledge and understanding, this paper engages and hopefully advances the methodological debate in the SDP literature.